Colorectal cancer and potential predictors of never screened for faecal occult blood test: a narrative review - Mohd Fazeli, Sazali; Syed Sharizman, Syed Abdul Rahim; Firdaus, Hayati; Andee Dzulkarnaen, Zakaria; Mohd Firdaus, Che Ani; Aini Fahriza, Ibrahim; Richard, Avoi (PAGEPress Italy, 2021)
Colorectal cancer (CRC) is a major public health threat. Therefore, CRC screening uptake has been a focus with the established precancerous lesion and the strong association of early detection with staging and survival of the disease. However, CRC screening is relatively low in many countries. This article briefly discussed the current situation of CRC, recommendations, and current uptake of CRC screening in various countries. Besides that, this article also highlights the potential factors that help to predict the CRC screening uptake worldwide. Identification of those factors could guide policymakers to develop an effective strategy to improve the CRC screening uptake and ultimately improve the health outcome of the population.